Ambivalent heroism? - Psychological burden and suicidal ideation among nurses during the Covid‐19 pandemic - Inken Höller; Thomas Forkmann (Wiley, 2022)
Abstract Aim During the Covid‐19 pandemic, the risk for nurses' mental health has rapidly increased. The two main goals of this study were the examination of (1) the psychological burden and (2) of suicidal ideation and its associated risk factors one year after the Covid‐19 pandemic begun. Design This was a cross‐sectional online survey. Methods N = 1311 nurses (96.9% female) aged 18-63 years (M = 30.96, SD = 8.48) were assessed for various symptoms of psychological burden, suicidal ideation and behaviour and its risk factors. Results Almost half of participants (41.5%) reported heightened levels of depressive symptoms, 691 (52.7%) reported a medium to high risk for burnout. One fifth of participants (21.7%) reported suicidal ideation in the past 4 weeks. The direct contact to people with Covid‐19 was not related to the extent of the psychological burden. Depression, agitation, perceived burdensomeness and previous suicide attempt were associated with suicidal ideation.